Navigating Uncertainty in Contemporary Romantic Relationships: A Systematic Review Based on Uncertainty Reduction Theory (2011-2023) - Zefira Fadryona; Andanareswari Wardhani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Uncertainty Reduction Theory (URT) explains how individuals experience and manage uncertainty in interpersonal interactions, particularly during the early stages of relationship development. However, uncertainty is not limited to initial encounters and can persist throughout ongoing relationships, including romantic relationships. This article aims to systematically review how Uncertainty Reduction Theory has been applied in the context of romantic relationships and to identify the types of uncertainty experienced by couples across different relational stages. Using a Systematic Literature Review (SLR) method guided by the PRISMA framework, this study analyzes seven national and international journal articles published between 2011 and 2023. The findings show that uncertainty in romantic relationships emerges not only during relationship initiation but also during maintenance, conflict, transitions, and dissolution. Couples experience uncertainty related to themselves, their partners, and the future of the relationship, which can influence emotional responses, communication patterns, and relational stability. The reviewed studies highlight the importance of communication strategies such as information seeking, self-disclosure, nonverbal cues, and digital communication behaviors in reducing uncertainty. Additionally, technological developments, including online dating and social media, introduce new forms of uncertainty while also offering alternative strategies for uncertainty reduction. This review demonstrates that URT remains a relevant and adaptable framework for understanding contemporary romantic relationships. The article also identifies gaps in existing research, particularly regarding long-term relationships and non-Western cultural contexts, and suggests directions for future studies.